Biodegradação anaeróbia da atrazina em diferentes condições de oxirredução - Matias, Tális Pereira (2019)
The indiscriminate use of atrazine herbicide in Brazil and worldwide has several adverse effects on human health and ecosystems, and can be found in soil, ground and surface water, in the air and also in living beings. The biodegradation of this compound can occur through different oxireduction conditions, with the participation of aerobic and anaerobic microbial consortia, generating different degradation metabolites intermediates. Through literature review and experimental research performed with enrichment of denitrifying microorganisms, sulfate reducing bacteria (BRS) and methanogenic arches, in anaerobic reactors under different oxirreduction conditions (denitrifying, sulfetogenic and methanogenic) the present work provides an explanation of the biodegradation of atrazine processes, highlighting the microorganisms detected in the literature with potential degradation of this compound using atrazine as carbon and / or nitrogen source, and its metabolite intermediates formed during the biochemical degradation processes. The methodology used in the experimental procedure consists of two distinct tests, the first called pure anaerobic reactors (RPA) and the second called anaerobic composite reactors (RCA). The two assays differ in the inoculum used and the carbon sources available in the reactors. In each trial 6 reactors were constructed for each different oxeduction condition, 3 biotic, 2 abiotic, and 1 blank (control). It was observed in this study that the removal of atrazine depends on biotic and abiotic factors, which may occur in both ways, and that physicochemical factors such as adsorption and chemical hydrolysis may have significant effects on this process. The results of the tests indicate that there was no variation in atrazine removal between different oxireduction media, 87% (± 7%) for the denitrifying condition, 88% (± 7%) for the sulfetogenic and 92% (± 7%). for methanogenesis, in biotic reactors with atrazine and soil organic content as the only carbon sources for bacteria in the reactors. However, the variation of the results found in RCA supplemented with complementary sources of acetate carbon for denitrifying reactors, lactate for sulfetogens and acetate and formate for methanogens, and reactors without this supplementation (RPA), indicates that high atrazine removal (100%) within 70 days of analysis for supplemented reactors should be done in shorter time periods.